Is a second debt crisis looming? - Lukas Menkhoff; Friedrich L. Sell (Intereconomics, 1986)
The debt crisis of the developing countries, which loomed so large at the beginning of the eighties, appears for the time being to have been overcome. However, under the surface problems are growing that could give a debt crisis among the developing countries an entirely new dimension. Under what conditions can a second debt crisis be prevented?
Keywords: 330; Indebtedness